2018
DOI: 10.1182/blood-2017-07-797597
|View full text |Cite
|
Sign up to set email alerts
|

Mutant JAK3 signaling is increased by loss of wild-type JAK3 or by acquisition of secondary JAK3 mutations in T-ALL

Abstract: K E Y P O I N T Sl One-third of T-ALL cases with JAK3 mutation harbor 2 JAK3 mutations.l Double JAK3 mutants show stronger signaling than single JAK3 mutants.The Janus kinase 3 (JAK3) tyrosine kinase is mutated in 10% to 16% of T-cell acute lymphoblastic leukemia (T-ALL) cases. JAK3 mutants induce constitutive JAK/STAT signaling and cause leukemia when expressed in the bone marrow cells of mice. Surprisingly, we observed that one third of JAK3-mutant T-ALL cases harbor 2 JAK3 mutations, some of which are monoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 22 publications
5
47
0
Order By: Relevance
“…23,49,50 Moreover, recent observation in cellular models have shown that wild-type JAK3 competes with the JAK3 mutants that require binding to the gc chain such as JAK3 M511I , JAK3 A572T , and JAK3 A573V , thus suggesting that these mutants are weak. 39 Here, we showed that heterozygous Jak3 KI/WT mice also develop a CTCL phenotype with a longer latency compared with homozygous Jak3 KI/KI . These in vivo results suggest that equal amounts of wild-type JAK3 do not prevent the development of T-cell malignancies.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…23,49,50 Moreover, recent observation in cellular models have shown that wild-type JAK3 competes with the JAK3 mutants that require binding to the gc chain such as JAK3 M511I , JAK3 A572T , and JAK3 A573V , thus suggesting that these mutants are weak. 39 Here, we showed that heterozygous Jak3 KI/WT mice also develop a CTCL phenotype with a longer latency compared with homozygous Jak3 KI/KI . These in vivo results suggest that equal amounts of wild-type JAK3 do not prevent the development of T-cell malignancies.…”
Section: Discussionmentioning
confidence: 66%
“…Of note, Jak3 KI/WT mice displayed a similar expansion of CD8 1 T cells albeit with longer latency (ie, in mice older than age 14 months) (supplemental Figure 3B,G), indicating a dosage effect of the Jak3 mutation on disease development, as has been recently observed in vitro. 39 These results indicate that endogenous expression of Jak3 A572Vactivating mutation induces, progressively and in a dose-dependent manner, a peripheral proliferation of malignant activated effector/ memory CD8 1 T cells with skin involvement closely resembling a leukemic form of human CTCL disorders (L-CTCL).…”
Section: Jak3 Ki/ki Mice Progressively Develop a Ctcl-like Disordermentioning
confidence: 70%
“…In addition, activating mutations in IL-7 receptor, JAK1, JAK3 , and STAT5 can be found in T-ALL, resulting in activation of JAK-STAT signaling [1,37]. Of note, IL-7 receptor mutations tend to be strongly activating alleles [38,39]; however multiple hits involving JAK1 and JAK3 mutations can be found in the same patient showing cooperative activity in the disease transformation [40]. In this context, inhibition of JAK-STAT can result in antitumor effects in preclinical models [40,41] (Figure 1).…”
Section: Targeting the Jak/stat Pathwaymentioning
confidence: 99%
“…Of note, IL-7 receptor mutations tend to be strongly activating alleles [38,39]; however multiple hits involving JAK1 and JAK3 mutations can be found in the same patient showing cooperative activity in the disease transformation [40]. In this context, inhibition of JAK-STAT can result in antitumor effects in preclinical models [40,41] (Figure 1). Importantly, the antileukemic effects of JAK-STAT inhibition do not seem restricted to leukemias harboring activating mutations in the pathway.…”
Section: Targeting the Jak/stat Pathwaymentioning
confidence: 99%
“…In addition, JAK3 exhibits high level of expression in leukemia ( Fig. S8) and it was found to be frequently mutated in T-cell acute lymphoblastic leukemia 29 . Furthermore, JAK3 was shown to function together with STAT3 to www.nature.com/scientificreports www.nature.com/scientificreports/ Table S1.…”
Section: Potential Roles Of Jak3 In Melanoma Progressionmentioning
confidence: 99%